Lentinula edodes based GIS mapping, biometabolites and antiinflamatory activity of wild edible mushrooms from tropical ‘sacred grove’ forests of Meghalaya, India - Khaund, Polashree; Joshi, S. R. (Revista de Biología Tropical, 2016)
The biodiversity rich state of Meghalaya, India located in the realms of mega-biodiversity hotspots, is home to numerous species of wild edible macrofungi that are used extensively by the mycophillic ethnic population, as a part of their traditional cuisine and medicine systems. However, habitat loss, due to deforestation and climate change, is destroying the natural population of these mushrooms, depleting their availability to the local communities. In the present investigation, a GIS guided habitat search, using Lentinula edodes as a representative species, was used in mapping the habitats of wild edible macrofungi of the study region. Sampling of around 4 000 specimens per distinct morphological type available in the traditional markets and “sacred grove” forests indicated presence of ten common genera, belonging to nine different families of wild edible mushrooms. Nutritional profiling of the representative species Lentinula edodes was carried out by evaluation of its moisture, total fat, crude protein and carbohydrates contents by standard methods. Similarly, bioactive components determination was performed by estimation of total phenols, flavonoids, ascorbic acid, β-carotene and lycopenes. Bioactivity of the mushrooms extracts was studied using the DPPH radical scavenging and Human Red Blood Cell (HRBC) membrane stabilization assays. The present investigation successfully attempted to explore remote sensing technologies and GIS (Geographic Information System) based system to predict the natural habitats of wild edible mushrooms of Meghalaya, India which we believe will lead to the generation of a mushroom specific non-wood forest resource mapping system in the near future. Results of nutritional profiling and biological activity studies on the representative species of wild edible mushrooms from the studied region revealed that it is a rich source of essential nutrients and antioxidants.